Pola Pencegahan Primer Stroke Oleh Pasien Hipertensi Di Rumah Sakit Muhammadiyah Palembang: Studi Deskriptif - Afriza Rianti; Sukron Sukron; Yulius Tiranda (Jurnal Keperawatan Muhammadiyah, 2019)
Background: Hypertension can lead stroke complications if not handled optimally. Disruption of blood flow causes the diameter of blood vessels of shrink, resulting in a lack of oxygen and glucose supply to the brain. Prevention is one of the best strategies to reduce the incidence of stroke. One of them is by implementing primary preventions such as regulating healthy food consumption, getting enouh rest, checking health regurarly, arranging nutrition diets, maintaining ideal body weight, doing physical activities regurarly, stop smoking, and avoiding drinking alcohol. Objective: To describe the primary preventions of stroke by hypertensive patients in Muhammadiyah Hospital of Palembang in 2019. Method: This was quantutative descriptive study using survey design. Result: Most of the respondents limited their consumption of foods containing excess salt (64.4%) and consumed protein foods regurarly such as fish (93.2%); all respondents consumed vegetables and fruits (100%), checked their health every month and did not consume alcohol. Conslusion: Primary prevention of stroke by hypertensive patients was considered as good category since they had a fairly healthy and good life behavior.